Carbon/nitrogen ratios determine biofilm formation and characteristics in model microbial cultures. (February 2023) - Ramos, Pia; Honda, Ryo; Hoek, Eric M.V.; Mahendra, Shaily
Abstract: The influence of growth medium water chemistry, specifically carbon/nitrogen (C/N) molar ratios, on the characteristics and development of biofilms of the model microorganism Pseudomonas aeruginosa was investigated. C/N = 9 had a unique effect on biofilm composition as well as quorum sensing (QS) pathways, with higher concentrations of carbohydrates and proteins in the biofilm and a significant upregulation of the QS gene lasI in planktonic cells. The effect of C/N ratio on total attached biomass was negligible. Principal component analysis revealed a different behavior of most outputs such as carbohydrates and QS chemicals at C/N = 9, and pointed to correlations between parameters of biofilm formation and steady state distribution of cells and extracellular components. C/N ratio was also shown to influence organic compound utilization by both planktonic and sessile organisms, with a maximum chemical oxygen demand (COD) removal of 83% achieved by biofilms at C/N = 21. Planktonic cells achieved higher COD removal rates, but greater overall rates after six days occurred in biofilms. The development of a dual-species biofilm of P. aeruginosa and Nitrobacter winogradskyi was also influenced by C/N, with increase in the relative abundance of the slower-growing N. winogradskyi above C/N = 9. These results indicate that altering operational parameters related to C/N would be relevant for mitigating or promoting biofilm formation and function depending on the desired industrial application or treatment configuration. Graphical abstract: Image 1 Highlights: Carbon/Nitrogen (C/N) affects biofilm chemical composition but not biomass attached. C/N influences quorum sensing (QS) relevant biomolecules, e.g. AHL production. Expression of QS genes in planktonic cells responds to C/N molar ratios in medium. Converging effects on biofilm formation and characteristics evidenced at C/N = 9. Multi-species biofilm is influenced by C/N, with dominance shift after C/N = 9.